Toward the lslamization of History: A Historical Survey (American Journal of Islam and Society, 2000)
History, or more properly the writing of history, had been during thetimes of the ancient Greeks and Romans an elitist activity, meant forglorifying the class of power, position, and birth. Parts of these historieswere fabulous in nature. The Muslims (Arabs) introduced the ideaof history as factual record. During the Middle Ages, history writingslipped into what it was in the Greco-Roman times. In the 16th century,the middle class, those with accumulated capital, wrote histories. Acolonial history, too, developed, enshrining a Euroean view of historythat still continues in school curricula. The 20th century saw changes.The writing of history became an imperialist necessity. When imperialismcollapsed, the focus disappeared. History became miniaturized andatomized. The entry of television and information technology broughtinstant histories. Islamic history writing accepts history as an instrumentof Allah's will and mode of living the good life.